Ba be bi bo bu a comparative study on English pronunciation of pre-school boys and girls - Ilagan, Lovejoy B.; Pugat, Florese S.; Castro, Maria Corazon Saturnina A. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2003)
This paper is a research on the differences in articulation of English sounds between preschool boys and girls. It aims to show not just the differences in how these two groups pronounce but also the factors which may affect the children's way of speaking. In gathering the data, the researchers conducted interviews and reading exercises among four and five year-old pupils from Claret School of Quezon City, Our Lady of Montichiari, and Holy Spirit School. These methods were used to extract what segmentals could the participants articulate and which ones they find difficult to pronounce. In analyzing the data gathered by the researchers, three theories were used. These theories are the Social Interactionist theory, the Phenome-by-Phenome theory, and the Feature-by-Feature theory. In applying these theories, the researchers were able to identify the factors which could affect children's pronunciation of English words - linguistic environment, social environment, and biological factors. The researchers also identified, through the Feature-by-Feature theory how children replace sounds they are supposed to produce with similar sounds.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.